Impact of Non-Reactive Ceria Nanoparticles on the Wettability and Reaction Kinetics Between Lead-Free Sn–58Bi and Cu Pad - Sharma, Ashutosh; Srivastava, Ashok K.; Lee, Kwan; Ahn, Byungmin (Metals and Materials International, 2019)
Lead-free Sn–58Bi–xCeO2 (x in wt% = 0, 0.3, 0.6 and 0.9) composite solder was prepared via mechanical blending and melting route. The ceria nanoparticles (CeO2) were prepared from chemical precipitation method. Further, the variation in microstructure and phase composition, melting point, wetting and mechanical properties were studied through scanning electron microscopy, energy dispersive spectroscopy, transmission electron microscopy, differential scanning calorimetry, spreading ratio, contact angle and tensile testing, respectively. It was shown that Sn–58Bi–xCeO2 composite solders show 16.66 and 32.05% increase in spread ratio and wetting angle, respectively, due to the enhanced melt fluidity up to x = 0.6. The fraction of hard Bi-phase was also refined simultaneously. The tensile results showed a slight decrease in ultimate tensile strength and enhancement in ductility up to x = 0.3 and 0.6 except at x = 0.9. High temperature aging also demonstrated a reduced intermetallic compounds thickness when fraction of ceria nanoparticles in the matrix was up to x = 0.6. It is suggested that for optimum set of soldering properties, the concentration of the nanoparticles should be at 0.6 wt% in the monolithic Sn–58Bi alloy.
Keywords: Ceria nanoparticles; Chemical precipitation method; Composite solders; High temperature aging; Mechanical blending; Melt fluidity; Spread ratio; Ultimate tensile strength; Bismuth; Composite solder; IMC; Nanoparticles; Spread ratio; Wetting